2009
DOI: 10.1007/s00213-009-1633-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific effects of escitalopram on neuroendocrine response

Abstract: This is the first study to prove that a single dose of escitalopram acts centrally and not peripherally, providing further support of the use of oral escitalopram as a probe for brain serotonergic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Neither the mechanism nor the significance of these findings is clear. Single doses of SSRIs have been demonstrated to increase plasma cortisol concentrations (47, 48); however, longer term studies have been less consistent with most studies finding plasma, salivary or urinary cortisol to either be unchanged or decreased after SSRI administration (42, 49-51). These longer term treatment studies have generally measured cortisol concentrations in the context of treating psychiatric disorders such as depression, generalized anxiety disorder or panic disorder, which are associated with increased cortisol concentrations (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…Neither the mechanism nor the significance of these findings is clear. Single doses of SSRIs have been demonstrated to increase plasma cortisol concentrations (47, 48); however, longer term studies have been less consistent with most studies finding plasma, salivary or urinary cortisol to either be unchanged or decreased after SSRI administration (42, 49-51). These longer term treatment studies have generally measured cortisol concentrations in the context of treating psychiatric disorders such as depression, generalized anxiety disorder or panic disorder, which are associated with increased cortisol concentrations (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of serotonin to these receptors leads to pupillary sphincter relaxation and thereby mydriasis 38 . The neuro‐endocrine findings also point in the direction of SERT binding, as other serotonergic compounds such as fenfluramine and escitalopram are known to respectively increase cortisol and cortisol and prolactin levels in healthy volunteers 9,11 . It could be argued that the endocrine effects can be caused by pituitary stimulation, outside the BBB and CNS.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition to the NeuroCart tests, serum cortisol and prolactin levels were measured as biomarkers for serotonergic effects, as escitalopram and citalopram are known to increase levels of these hormones. 9 Although it is uncertain whether growth hormone levels are influenced by serotonergic compounds, 10 serum growth hormone levels were also measured.…”
Section: Introductionmentioning
confidence: 99%
“… 4) One study comparing citalopram and escitalopram showed that after a single dose, escitalopram acted centrally (and not peripherally) and increased prolactin and cortisol levels while also exhibiting successful blockade of cortisol following administration of dexamethasone. 5) …”
Section: Discussionmentioning
confidence: 99%